Macroprolactin; A Frequent Cause of Misdiagnosed Hyperprolactinemia in Clinical Practice - R Vaishya; R Gupta; S Arora (JRI, 2010)
Introduction: Macroprolactin is a significant cause of misdiagnosis, unnecessary investigation, and inappropriate treatment in patients with hyperprolactinemia. Its frequency has not been clearly established due to technical difficulties in identifying it. Most laboratories and clinicians are unaware of macroprolactin interferences in prolactin assays. Materials and Methods: A comprehensive literature search was conducted on the websites of the National Library of Medicine (http://www.ncbl.nlm.nih.gov) and PubMed Central, the US National Library of Medicine’s digital archive of life sciences literature (http://www.pubmedcentral.nih.gov/). The data were also looked for in relevant books and journal. Results: Macroprolactin is a non-bioactive prolactin isoform usually composed of a prolactin monomer and an IgG molecule having a prolonged clearance rate similar to that of immunoglobulins. This isoform is clinically non-reactive but it interferes with immunological assays used for the detection of prolactin. Conclusion: There is a need to understand and explore the recent progress in the diagnosis and pathophysiology of macroprolactinemia for improving patient care.
Keywords: Hyperprolactinemia, Macroprolactin, Polyethylene glycol assay, Prolactin antibody